Teologi kerja: Kerja sebagai realitas panggilan yang berpusat pada Allah - Panggabean, Justice Zeni Zari (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2023)
Various work morality issues relate to job satisfaction and comfort. Work is also, in reality, associated with social status. As a result, work is only seen as a certain necessity. On the other hand, work is God's mandate to humans who are given the power to maintain the integrity of His creation. This research will aim to outline: first, the definition of work theology in its context; second, the attitude and calling to work in carrying out God's mandate; and third, the reality of work that is centered on God. In response to this mandate and calling, work theology shows that work attitudes and callings should be centered on God. The research method uses a qualitative approach that describes literature from several theories related to work theology. The result of the discussion in this article is that work theology builds a human perspective to view work in the light of God's insight, purpose, and involvement. This research concludes that work is a calling in the form of acceptance, care, and understanding as God's gift to humans. A calling to work is a mandate to continue God's work.Â AbstrakBerbagai persoalan moralitas kerja berkaitan dengan kepuasan dan kenyamanan kerja.Â Kerja juga dalam realitasnya dikaitkan dengan status sosial. Akibatnya, kerja hanya dipandang sebagai sebuah kebutuhan tertentu. Di sisi lain, kerja adalah mandat Allah kepada mansusia yang diberi kuasa untuk menjaga keutuhan ciptaan-Nya. Tujuan penelitan ini akan menguraikan: pertama, definisi teologi kerja dalam konteksnya; kedua, sikap dan panggilan kerja dalam melaksanakan mandat Allah; ketiga, realitas kerja yang berpusat pada Allah. Sebagai respon akan mandat dan panggilan itu, teologi kerja menunjukkan bahwa sikap dan panggilan kerja seyogianya berpusat pada Allah. Metode penelitian menggunakan pendekatan kualitatif yang menguraikan literatur dari beberapa teori terkait dengan teologi kerja. Hasil pembahasan dalam tulisan ini adalah teologi kerja membangun perspektif manusia untuk memandang pekerjaan dalam wawasan, tujuan dan keterlibatan Allah. Penelitian ini membangun kesimpulan bahwa pekerjaan adalah panggilan dalam bentuk penerimaan, pemeliharaan dan pemahaman sebagai anugerah Allah untuk manusia. Panggilan kerja dimaknai sebagai mandat melanjutkan karya Allah. Â